1971
DOI: 10.1037/h0031293
|View full text |Cite
|
Sign up to set email alerts
|

Behavior therapy in retrospect: Patients' feelings about their behavior therapies.

Abstract: Fourteen behavior therapy patients were interviewed to determine if phenomena regularly observed in psychodynamic psychotherapies had occurred in their behavior therapies as well. Interview data were analyzed both statistically and clinically. Ratings by patients, their therapists, and the Es indicated that the prevalence of behavior modification techniques in the therapy was not significantly related to outcome, whereas a variety of the patients' personal feelings about their therapists were. Impressionistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1
1

Year Published

1976
1976
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 35 publications
3
43
1
1
Order By: Relevance
“…This authority was reassuring apparently because it gave the clients a sense of safety against potential aggression from other participants. In agreement with studies on other populations (Ryan & Gizynski, 1971;Schindler, Hohenberger-Sieber, & Hahlweg, 1989), the patients' definition of a good therapist involved confidence, strength, competence, and persuasiveness when necessary.…”
Section: Preliminary Studiessupporting
confidence: 58%
“…This authority was reassuring apparently because it gave the clients a sense of safety against potential aggression from other participants. In agreement with studies on other populations (Ryan & Gizynski, 1971;Schindler, Hohenberger-Sieber, & Hahlweg, 1989), the patients' definition of a good therapist involved confidence, strength, competence, and persuasiveness when necessary.…”
Section: Preliminary Studiessupporting
confidence: 58%
“…In five retrospective studies, patients were asked what they felt had been the most helpful aspect of their cognitive-behavioral treatment (Llewelyn & Hume, 1979;Murphy, Cramer, & Lillie, 1984;Ryan & Gizynski, 1971;Sloane, Staples, Whipple, & Cristol, 1977;van Beek, 1996). All five studies consistently reported that patients had found the relationship with their therapist more helpful than the cognitivebehavioral techniques that were employed.…”
Section: Therapist Behavior Empathy Warmth Positive Regard and Genmentioning
confidence: 99%
“…When patients who have completed cognitivebehavioral treatment are asked to indicate what had helped them the most to overcome their problems, they will answer "talking with somebody who listens and understands." (Llewelyn & Hume, 1979;Murphy et al, 1984;Ryan & Gizynski, 1971;Sloane et al, 1977;van Beek, 1996). …”
Section: Conclusion and Further Elaborationsmentioning
confidence: 99%
“…By obtaining reports from clients rather than therapists, they were able to show that what happens in behaviour therapy and in traditional psychodynamic treatment has more in common than most behaviour therapists like to suppose. (Ryan and Gizynski, 1971). The latter, at times, seem to make great efforts to give the appearance of engaging in a scientific exercise.…”
Section: Potency and Schools Of Psychotherapymentioning
confidence: 93%